Particulate Matter in a Hospital Environment: as Potential Reservoir for Hospital Strains - E. A. Chezganova; O. S. Efimova; S. A. Sozinov; A. R. Efimova; V. M. Sakharova; A. G. Kutikhin; M. V. Osnova; Z. R. Ismagilov; E. B. Brusina (Эпидемиология и вакцинопрофилактика, 2019)
Relevance. For decades, many aspects of aerosol transmission of hospital pathogens have been and remain the subject of scientific debate. Despite fairly detailed studies of the mechanism of microbial aerosols formation, distribution, the role of particulate matter in the formation of antibiotic resistance and multidrug-resistant hospital clones of microorganisms is still unclear. Aim. To investigate physicochemical properties and microbiological diversity of hospital particulate matter. Materials and Methods. Shape and size of particulates was assessed by means of scanning electron microscopy and dynamic light scattering while elemental analysis was performed using energy-dispersive X-ray spectroscopy and high-temperature catalytic oxidation. Microbial profiling was conducted using polymerase chain reaction and Vitek 2 biochemical analyzer. Results. Hospital particulate matter included globular and fibrillary particles consisting of carbon, oxygen, calcium, silicon, aluminium, and sulfur. Intriguingly, microfiber particles had higher oxygen and calcium content along with the lower level of carbon in mineral but not organic component. Differential localisation of silicon and calcium in elemental mapping suggested that hospital particulate matter was composed of aluminosilicate minerals and calcium compounds. Among the microorganisms, we found multidrug-resistant strains Raoultella ornithinolytica, Staphylococcus pseudintermedius, Pantoea spp., Pseudomonas aeruginosa, Enterococcus faecium and additionally Pasteurella canis in hospital particulate matter samples. Conclusions. Particulate matter in the hospital environment might be considered as a potential reservoir for the evolution of antibiotic resistance and multidrug-resistant strains.